Adaptive robust control of coupled attitude and orbit for spacecraft with model uncertainties. Issue 1 (2nd January 2018) - Sun, Jun; Wu, Xiande; Zhang, Shijie; Guo, Fengzhi; Song, Ting
Abstract : Purpose: The purpose of this paper is to propose an adaptive robust controller for coupled attitude and orbit control of rigid spacecraft based on dual quaternion in the presence of external disturbances and model uncertainties. Design/methodology/approach: First, based on dual quaternion, a theoretical model of the relative motion for rigid spacecraft is introduced. Then, an adaptive robust controller which can realize coordinated control of attitude and orbit is designed in the existence of external disturbances and model uncertainties. Findings: This paper takes advantage of the Lyapunov function which can guarantee the asymptotic stabilization of the whole system in the existence of parameters uncertainties. Simulation results show that the proposed controller is feasible and effective. Originality/value: This paper proposes a coupled attitude and orbit adaptive robust controller based on dual quaternion. Simulation results demonstrate that the proposed controller can achieve higher control performance in the presence of parameters uncertainties.